PENGARUH JOB DESCRIPTION, KEPEMIMPINAN, PENGEMBANGAN TERHADAP EFEKTIFITAS KERJA KARYAWAN PT. BIAS NUSATAMA WAREHOUSE MINAS - Ridho Nandika; Marzolina '; Nuryanti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study was conducted at PT Bias Nusatama Warehouse Minas. Aims to determine the effect simultaneously and partially Job Description, Leadership, and Employee Development Effectiveness Against PT Bias Nusatama Warehouse Minas.There are three variables: the dependent variable and two independent variables. The study was conducted with a sample of 73 people. Research using test equipment and multiple regression analysis using census techniques by givingquestionnaires to the respondents. In terms of data analysis, using qualitative and quantitative methods using SPSS (Statistical Package for Social Sciences) version 20.0.The leadership and management of PT Bias Nusatama Minas in order to increase the variable Warehouse Job Description, Leadership, Development and Analysis office is by employees before being placed in that position and put the employee in accordance science and experience, by placing a Project Managerwho has a high intelligence in the lead of the employees, and enhance the development of variables, namely by providing moral support of the working environment to the employees.Keywords: Job Description, Leadership, Development, and Work Effectiveness